Social cohesion, internal efficacy, and external efficacy: Studying voting behavior using collective efficacy theory. Issue 5 (19th October 2020) - Gearhart, Michael C.
ABSTRACT: Collective efficacy theory is a widely used theoretical framework for explaining how social cohesion is activated as collective actions. Because collective efficacy was developed as a criminological theory, the majority of collective efficacy research focuses on the relationship between social cohesion and informal social control. Conceptually, social cohesion can be activated as civic participation – particularly voting. Although research examining voting behavior through a collective efficacy framework is scarce, findings suggest that collective efficacy is a useful framework for explaining civic participation. However, previous research is limited because it lacks key predictors of voting – namely internal efficacy and external efficacy. This study examines the relationships among social cohesion, internal efficacy, and external efficacy using a nationally representative sample of voters. Findings support collective efficacy as a useful framework for increasing civic participation. Further, social cohesion, internal efficacy, and external efficacy are key factors predicting civic participation.